Characterisation and treatment of waste water from a centrifuge rubber latex concentration unit - Madhu G; George K E; Joseph Francis D (Indian Journal of Natural Rubber Research, 1991)
Characterisation of the waste water from a centrifugal latex concentration unit was carried out. Conventional coagulants were tried to remove turbidity and chemical oxygen demand (COD) of the waste water. Aluminium chloride was found to be the best for the removal of both turbidity and COD.
Keywords: Centrifugal latex concentration; Centrifugal latex concentration; Coagulants; Coagulants; Effluent treatment; Effluent treatment; Natural rubber; Natural rubber; Turbidity; Turbidity; Waste water; Waste water